Social Adjustment of persons with Schizophrenia in Rural Areas - An Intervention Study - Ponnuchamy, L. (International Journal of Psychosocial Rehabilitation, 2015)
The intervention to improve these deficits is inadequate in rural areas in India. Aims: The aim is to ascertain impact of structured social work intervention for management of social adjustment of persons with schizophrenia in rural areas. Methods: The sample consisted of thirty persons with schizophrenia and significant family members. A proportionate sample covering heterogeneous socio demographic background was drawn using simple random sampling technique. It was followed a Before-After Experimental Research Design Without Control Group. The social adjustment was assessed before and after social work intervention using Katz Social Adjustment Scale. Results: After social work intervention overall there were changes in social adjustment domains. The performance of social activities of patient and free time activities of patient had increased significantly. Further expectations of family members had decreased and satisfaction of family members had increased significantly. The results have indicated that the social work intervention has contributed to improve the social functioning of the patients in rural areas. Conclusion: Results have shown the changes in all the domains of social adjustment significantly. Conducting similar studies in different settings would contribute to the social work knowledge in future.